2020
DOI: 10.1186/s12889-020-08719-0
|View full text |Cite
|
Sign up to set email alerts
|

Expanding access to HIV testing through Canadian community pharmacies: findings from the APPROACH study

Abstract: Background There is a need for acceptable and feasible HIV testing options to ensure people living with HIV know their status so they can access care. Pharmacist-provided HIV point-of-care testing (POCT) may overcome testing barriers, including privacy concerns, testing wait times, and improve accessibility. In the APPROACH study, we aimed to develop and assess an HIV POCT program in community pharmacies for future scale up and evaluation. This paper describes the program uptake, participant and pharmacist exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…42 44 HIV Among the seven studies focused on HIV, one evaluated pharmacist-led pre-exposure prophylaxis (PrEP), 51 and the remainder focused on HIV screening at the community pharmacy. [52][53][54][55][56][57] Havens et al implemented a pilot whereby individuals started on HIV PrEP could choose to be followed by a pharmacist for ongoing sexually transmitted infections (STI)/HIV screening, follow-up, and PrEP prescribing. 51 Although the authors described logistical challenges related to STI screening, results indicated that implementing a pharmacist-led PrEP programme was feasible and achieved high satisfaction rates among participants.…”
Section: Chlamydiamentioning
confidence: 99%
See 2 more Smart Citations
“…42 44 HIV Among the seven studies focused on HIV, one evaluated pharmacist-led pre-exposure prophylaxis (PrEP), 51 and the remainder focused on HIV screening at the community pharmacy. [52][53][54][55][56][57] Havens et al implemented a pilot whereby individuals started on HIV PrEP could choose to be followed by a pharmacist for ongoing sexually transmitted infections (STI)/HIV screening, follow-up, and PrEP prescribing. 51 Although the authors described logistical challenges related to STI screening, results indicated that implementing a pharmacist-led PrEP programme was feasible and achieved high satisfaction rates among participants.…”
Section: Chlamydiamentioning
confidence: 99%
“…55 Studies that focused on HIV screening demonstrated pharmacists are capable of reaching high-risk groups and individuals not previously tested. [52][53][54][55][56][57] Crawford et al evaluated uptake of HIV testing when part of comprehensive disease screening implementation in low access and minority communities. 53 Kelly et al and Fernández-Balbuena et al found as low as 27% and as high as 52% of individuals reported they were not previously tested for HIV (or were unsure).…”
Section: Chlamydiamentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from the GetaTest pilot project demonstrate the acceptability and feasibility of pharmacy-delivered HIV POCT, which is consistent with findings from the APPROACH study. 13 This pilot successfully increased rates of HIV testing for members of populations most affected by HIV and for people who had not previously tested for HIV. GetaTest also highlighted the critical role that pharmacists play in expanding access to HIV testing, the key first part of the HIV care cascade.…”
Section: Discussionmentioning
confidence: 99%
“…POC testing programs in a variety of settings have been shown to be acceptable, feasible and an important engagement tool for testing and linkage to care [ 2 ]. Models of delivering POC testing include primary care, STI clinics, community-based organizations and emergency departments [ 2 ], and have more recently expanded to pharmacies [ 3 ]. Additionally, home-based POC testing was licensed for use and sale in Canada in November 2020 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%